2013
DOI: 10.1590/2237-6089-2013-0019
|View full text |Cite
|
Sign up to set email alerts
|

The broad autism phenotype in parents of individuals with autism: a systematic review of the literature

Abstract: The broad autism phenotype (BAP) is a milder manifestation of the defining symptoms of the syndrome in individuals without autism. This study conducted a systematic review of studies about behavioral characteristics of interpersonal relationships, communication and rigidity, as well as about three cognitive models, Theory of Mind, central coherence and executive function, in parents of individuals with autism. The indexed databases were LILACS, IBECS, Web of Science, and MEDLINE, and the studies retrieved were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 52 publications
2
27
0
2
Order By: Relevance
“…Cruz et al (2013) reviewed studies of BAP in parents of individuals with ASD and found widely varied BAP symptoms in parents, including pragmatic language impairment, lack of friends, difficulties in planning, impaired working memory, and impaired detection of emotions in face expressions. Cruz et al (2013) also noted a great variation in BAP symptom prevalence, ranging from no parent deficits in skills such as reading and spelling to more than 40 % of parents expressing some form of pragmatic language deficit.…”
Section: Rates Of Recovery From Asd Are Variedmentioning
confidence: 99%
“…Cruz et al (2013) reviewed studies of BAP in parents of individuals with ASD and found widely varied BAP symptoms in parents, including pragmatic language impairment, lack of friends, difficulties in planning, impaired working memory, and impaired detection of emotions in face expressions. Cruz et al (2013) also noted a great variation in BAP symptom prevalence, ranging from no parent deficits in skills such as reading and spelling to more than 40 % of parents expressing some form of pragmatic language deficit.…”
Section: Rates Of Recovery From Asd Are Variedmentioning
confidence: 99%
“…their parents and siblings. Broader autism phenotype is defined as a set of specific social and communication skills as well as personality features, considered to be a 'lighter' expression of features characteristic for autism (Cruz et al, 2013;Sucksmith, Roth, & Hoekstra, 2011). It is important to note that BAP does not constitute a separate diagnostic entity -difficulties observed in families of individuals with ASD are too mild to fulfil the criteria needed to be defined as a disorder (Gerdts & Bernier, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Bolton and his co-workers (1994) determined their presence in about 12.40% of individuals from that group and only in 1.60% of siblings of people with Down syndrome (DS). In their systematic literature review, Cruz et al (2013) concluded that BAP occurs in 12-30% of siblings of individuals with ASD. Most studies indicate that at least half of the relatives of people with ASD do not show any deficits in the analysed areas, which suggests that features associated with BAP occur in a subgroup of the family members (Gerdts & Bernier, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, executive functions (EFs) consist of a set of cognitive skills that, when associated, are designed to execute an oriented behavior towards previously established purposes, thus allowing the individuals to directly interact with the world and to organize tasks, such as setting goals, evaluating the efficiency and adequacy of the behavior according to situations, and abandoning improper strategies for the sake of more appropriate or convenient ones to solve problems (Cruz, Camargos-Junior, & Rocha, 2013;MalloyDiniz et al, 2010;Sesma, Mahone, Levine, Eason, & Cutting, 2009;Tonietto, Wagner, Trentini, Sperb, & Parente, 2011;Yasumura, Inagaki, & Hiraki, 2014). EFs are responsible for articulating subordinated functions such as thinking, working memory, planning, attention and inhibitory control, and cognitive flexibility, among others, which guide the execution of a behavior with specific aims (Ferrier, Bassett, & Denham, 2014;Miyake & Friedman, 2012;Olaithe & Bucks, 2013;Skogan et al, 2015).…”
mentioning
confidence: 99%